2017
DOI: 10.1111/jep.12725
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐led education and cognitive behaviour therapy‐based intervention among adults with uncontrolled type 2 diabetes: A randomised controlled trial

Abstract: At 6 months post intervention, HbA was reduced in both intervention groups with a greater reduction noted in the nurse-led education intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 23 publications
(36 reference statements)
0
87
0
Order By: Relevance
“…Nine (2.2%) RCTs [ 21 29 ] confirmed inclusion of people with SMI following email requests; however, of these, only six [ 21 23 , 25 , 28 , 29 ] provided data on the numbers recruited and none provided data on effectiveness of the interventions in their participants with SMI. The six trials that provided data recruited a total of 1009 participants with T2DM, of whom 31 (3.1%) had SMI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine (2.2%) RCTs [ 21 29 ] confirmed inclusion of people with SMI following email requests; however, of these, only six [ 21 23 , 25 , 28 , 29 ] provided data on the numbers recruited and none provided data on effectiveness of the interventions in their participants with SMI. The six trials that provided data recruited a total of 1009 participants with T2DM, of whom 31 (3.1%) had SMI.…”
Section: Resultsmentioning
confidence: 99%
“…The six trials that provided data on participants with SMI were conducted in Brazil [ 23 ], New Zealand [ 28 ], Qatar [ 22 ], Slovenia [ 29 ] and the United States [ 21 , 25 ]. The interventions they evaluated were varied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A wealth of data support the importance of nurses in patient and caregiver education. Research has found that nurse-led education can support overall patient and caregiver well-being, 33 activation, 34,35 and knowledge retention. 34 Nurses also play a role in coaching patients and caregivers through self-care and instructions on disease management, 36,37 areas that the present study identified as distinct needs of patients to drive patient experience.…”
Section: Expertise Patients Perceiving They Are Being Cared For Bymentioning
confidence: 99%
“…3 , 4 Key to the management of diabetes according to the American Diabetes Association Standards of Medical Care in Diabetes 5 is glycemic control, and this underpins the prevention of acute and long-term complications. Maintaining glycemic control through a combination of medication and/or lifestyle remains challenging for many people living with type 2 diabetes 6 and linked to long-term complications. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%